2023
DOI: 10.3390/ijms242115551
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting as a Potential Therapeutic Instrument for Major Depression Disorder: A Systematic Review of Clinical and Preclinical Studies

Laís Murta,
Daniela Seixas,
Luana Harada
et al.

Abstract: Recent studies have reported positive effects of Intermittent Fasting (IF) on metabolic parameters, cognition, and mood. However, regarding depressive symptoms, the effect of IF is not clear. The purpose of this review was to assess the available evidence on IF interventions for depression in both clinical and preclinical studies. Of the 23 included studies, 15 were performed on humans and 8 on animal models. The studies on rodents suggested that IF acts as a circadian regulator, improving neurotransmitter ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Such mechanisms may contribute to the anti-depressive effects of fasting interventions (Berthelot et al, 2021;Murta et al, 2023). Taken together, capitalizing on metabolic signals might provide better treatments for motivational deficits in depression (Ferstl et al, 2022(Ferstl et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such mechanisms may contribute to the anti-depressive effects of fasting interventions (Berthelot et al, 2021;Murta et al, 2023). Taken together, capitalizing on metabolic signals might provide better treatments for motivational deficits in depression (Ferstl et al, 2022(Ferstl et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Melancholic MDD is associated with HPA hyperactivity (Lamers et al, 2013), and preclinical studies have shown that ghrelin regulates stress-induced anxious behavior via the HPA axis (Spencer, 2012), supporting a link between homeostatic signals and affective states (Fahed et al, 2023) . Such mechanisms may contribute to the anti-depressive effects of fasting interventions (Berthelot et al, 2021; Murta et al, 2023). Taken together, capitalizing on metabolic signals might provide better treatments for motivational deficits in depression (Ferstl et al, 2022, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…There is also recent evidence that chrononutrition behaviors such as TRE or TRF may have a potential impact on emotional state and mood. In this aspect, Murta et al, have suggested that IF may exert positive effects for the treatment of mood disorders [ 61 ]. However, most of the available clinical trials have specific limitations, such as small sample sizes and uncontrolled designs, highlighting the need to perform better-designed studies and controlled evaluations to assess its efficiency in the treatment of major depression [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The particular limitations of most clinical trials that are currently available include small sample sizes and uncontrolled designs. Although IF may have physiological effects that could be important in mood disorders, more thorough research and controlled trials are required to determine whether or not IF is effective in treating major depression, especially in psychiatric patients [135]. In fact, only two systematic reviews have been published to date [130,136], including a limited number of analyzed studies.…”
Section: If and Mental Healthmentioning
confidence: 99%